Urgensi dan Aplikasi Qawa’id Al-Fiqhiyyah tentang Konsep ‘fii Al-Akhdzi Bi Ar-Rukhsoh’ Dalam Pengembangan Ekonomi Syariah - Yudi Permana; Lenny Yanthiani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2020)
This research is aimed to identify the urgency and the use of the concept of ‘Fii al-Akhdzi Bi Ar-Rukhsoh’ in the development of Islamic Economics. As we know, the Islamic economics field is classified as the Muamalah field which has possibility to be developed with different approaches. The research methodology which was used in this study used the qualitative and library research approaches, including Arabic, English and Indonesian literature. The result showed that the concept of Fii al-Akhdzi Bi Ar-Rukhsoh can be one of qawaids to develop Islamic economics. For example: The concept can be applied to answer the hukm of debt trading, and others.